Academic trip to Sabah (KK) - Kueh, Dorothy Chiok Choo (UiTM Sarawak, 2016)
As part of the requirement of the course for BM242, an academic trip was organised by a group of 31 Part 5 BBA (Fin.) studentsto visit institutions such as the Sabah Credit Corporation,SEDiA and Yayasan Sabah from 9th to 10th November, 2015. At the institutions, the students were briefed and given talks about entrepreurship. The students found the trip inspiring and motivational. Team building was instilled among the students and the lecturer accompanying the students was Pn Norzaihan Hashim.